Khumba = Cesur Zebra - Silverston, Anthony, director (Cinema Management Group, 2013)
Rejected by his superstitious herd, a half-striped zebra embarks on a daring quest to earn his stripes but finds the courage and self-acceptance to save all the animals of the Great Karoo.
PG.
Region 2.
K-3.
Language : Turkish, English.
Subtitle : Turkish.
Keywords: Motion pictures -- Kids/Family Films; Movie -- animated films; Zebra -- Movie